Analisis karakteristik kinerja dan tingkat pelayanan pada ruas jalan dengan bukaan median - Kunna, A Sarwono Suhar; Said, Lambang Basri; Maryam, St (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study aims to analyze the effect of U-Turn facilities on traffic performance on Makassar Perintis Kemerdekaan Road, with a focus on three study points, namely KM 8+327 (in front of PO Bintang Marwah Bus), KM 10+467 (in front of Yonkav TNI Dormitory), and KM 10+910 (in front of Cokroaminoto Campus Makassar). The method used in this research is quantitative analysis based on the Indonesian Road Capacity Manual (MKJI, 1997). Data were collected through traffic surveys for three days during peak hours (07:00-09:00, 11:00-13:00, and 15:00-18:00), including vehicle volume, travel time, vehicle speed, queue ratio, road capacity, and degree of saturation. The results showed that the presence of U-Turns on the Makassar Perintis Kemerdekaan Road Section has a significant impact on increasing traffic delays and decreasing the level of road service. High vehicle volumes, especially during peak hours, cause long queues at U-Turn locations, with degree of saturation (DS) values approaching or exceeding the threshold suggested by MKJI. In addition, it was found that the presence of "mr. ogah" who regulates traffic unofficially also worsens traffic flow conditions by creating conflicts between vehicles by causing queues characterized by the highest queue ratio of 1.34 at Km 8 + 327 then the queue ratio at km 10 + 467 of 1.16 and the queue ratio at km 10 + 910 of 1.067. The conclusion of this study is the need for evaluation and rearrangement of U-Turn facilities to improve the efficiency of traffic flow on the Makassar Independence Pioneer Road Section. Some of the recommendations proposed include the addition of special lanes for U-Turns, increasing road capacity, and installing clearer signs and road markings to reduce traffic conflicts.